2001
DOI: 10.1521/suli.31.1.83.21315
|View full text |Cite
|
Sign up to set email alerts
|

Do They Suffer More? Reflections on Research Comparing Suicide Survivors to Other Survivors

Abstract: This article contrasts public perceptions of suicide survivors with conclusions based on comparative studies of suicide, fatal accident survivors, and other survivors. Although suicide is commonly thought to cause a particularly burden-some grief, quantitative studies have often failed to support this. We then offer some interpretations of these findings and suggest future pathways for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 30 publications
0
54
1
1
Order By: Relevance
“…Deaths which are sudden and unexpected will tend to impose a greater burden on the bereaved (Cleiren et al, 1994;Parkes & Weiss, 1983;Rynearson, 1987). However, other research has formed different conclusions and argued that positing similarities between suicide bereavement and unnatural death bereavements collectively, creates a 'diluting' of any distinct differences (Ellenbogen & Gratton, 2001;Jordan, 2001).…”
Section: Problems Of Differentiating Grief: Quantitative Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Deaths which are sudden and unexpected will tend to impose a greater burden on the bereaved (Cleiren et al, 1994;Parkes & Weiss, 1983;Rynearson, 1987). However, other research has formed different conclusions and argued that positing similarities between suicide bereavement and unnatural death bereavements collectively, creates a 'diluting' of any distinct differences (Ellenbogen & Gratton, 2001;Jordan, 2001).…”
Section: Problems Of Differentiating Grief: Quantitative Studiesmentioning
confidence: 99%
“…Several authors such as Ellenbogen and Gratton (2001) and Clark (2001) have identified that the majority of studies that have failed to find any fundamental differences in the grief experienced after suicide, have primarily utilised quantitative methodological approach. They argue a number of the conventional research methods used are insensitive to qualitative differences unique to suicide grief and it is consequently, and mistakenly, assumed that differences in the mourning process between suicide and other types of losses fail to exist (Ellenbogen & Gratton, 2001;Jordan, 2001).…”
Section: Problems Of Differentiating Grief: Quantitative Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[Demi, 1984;Barrett und Scott, 1990;Rudestam, 1992]. Auch konnte man keine nur für die Trauer nach Suizid charakteristischen Reaktionen der Hinterbliebenen identifizieren [Ellenbogen, 2001]. Man geht inzwischen davon aus, dass nach einem Suizid die Trauer selbst nicht notwendigerweise viel tiefer ist, sondern dass bestimmte Charakteristika den Verarbeitungsprozess erschweren können [McIntosh, 1993;Jordan, 2001;Harwood et al, 2002] [Dunne, 1992;Bürgin, 2001].…”
Section: Definition Und Beschreibung Von «Suizidhinterbliebenen»unclassified